Intervention Plan of the Psychosocial Care Network of the Regional Health Superintendence of Teófilo Otoni/Minas Gerais/Brazil (Research, Society and Development, 2022)
The Psychosocial Care Network (RAPS) is composed of several community-based services that aims to ensure the free movement of people with psychological distress and/or mental disorders through services and the community. This study aims to develop an Intervention Plan for the expansion of RAPS of the Regional Health Superintendence (SRS) of Teófilo Otoni. This is a bibliographic research developed based on material published in books; scientific journals; official websites of the Ministry of Health (MS) and the State Department of Health (SES) of Minas Gerais. It was evident in this study that the RAPS of the SRS of Teófilo Otoni/MG does not have in its totality the substitute services to sustain the work in an articulated way, as well as the main obstacle pointed out by the managers refers to the financial difficulty. The Intervention Plan is intended for the implementation of services related to the Specialized Psychosocial Care Component and the Hospital Care Component, and is a guide tool of planning that will be implemented in the SRS of Teófilo Otoni, in accordance with the State Policy of Mental Health, Alcohol and other Drugs of Minas Gerais, aiming to fill the care gaps and expand the coverage of care.